O controle da subjetividade nas decisões judiciais em casos de colisão entre direitos fundamentais: hermenêutica, método e a tensão entre o racional e o irracional - Nepomuceno, Raul Carneiro (2019)
The research discusses the role played by feelings in the interpretation of fundamental rights, in an analysis performed from the perspective of cognitive sciences, behavioral psychology and neurosciences. It begins by showing that the mental activity of interpretation is only possible within a cultural context historically constituted and marked by affections, both in the origin and in the maintenance of intersubjective bonds of meaning. Next, it emphasizes that the cognitive activity itself is based on the body, so that the knowledge of objects is given only through the mediation not only of historical consciousness and language, but also of the body states that constitute the consciousness and cognitive experience as such. It is also emphasized that the knowledge and interpretation of law in general, and of fundamental rights in particular, not only involves normative statements and precedents, but also facts conditioning the application of law, values, reports and even the evaluation of people involved, so that the spaces for the influence of personal beliefs, ideology, prejudices, expectations, in short, instances of human experience that are deeply affective are expanded. Starting from the idea that every interpretation of the law is also an application, and consequently involves a decision, the decision-making process is presented as also marked by emotions, which collaborate in the elimination of decision-making options and the formation of biases and heuristics from which decisions are taken. Some biases and heuristics that can decisively affect the interpretation of legal cases are analyzed, especially those involving the attribution of weights to fundamental rights. The problem of discretionary legal interpretation is also faced, and attempts are made to demonstrate that the theoretical models and the methods and principles of specifically constitutional interpretation that emerged in the second post-war period do not resolve – nor can they resolve – this problem satisfactorily, but have, on the contrary, accentuated it. It is a qualitative research, mainly bibliographic, but which makes use of experimental research in the field of Behavioral Psychology and Behavioral Economics, as well as of decisions rendered by national courts.